First report of the presence of Trypanosoma evansi in dogs from Paraguay applying molecular techniques - Salvioni Recalde, Oscar Daniel; Fraenkel, Stefanía; José Tintel, María; Arze, Verónica Paola; Ramírez Centurión, Natalia; Rolón, Miriam; Vega Gómez, Celeste (Brazilian Journal of Veterinary Medicine, 2021)
Surra is a disease caused by the hemoflagellate pathogen Trypanosoma evansi which affects a wide variety of mammals. The only cases reported of the presence of T. evansi in Paraguay were identified in samples from horses and capybaras and they were detected by light microscopy in the 19th century. The aim of this study is to report three autochthonous cases of canine trypanosomiasis caused by T. evansi, for the first time in the country, using molecular techniques and their application for the differential diagnosis of trypanosomatids species. The technique implemented was real-time PCR-HRM, amplifying a fragment of the hsp70 gene, using a pair of primers initially used to discriminate Leishmania species. This is the first report on the usage of these primers to detect T. evansi through HRM analysis, which allows the differentiation of trypanosomatids species simultaneously, making it an efficient tool for differential diagnosis.